A resonant damping control and analysis for LCL-type grid-connected inverter. (November 2022) - Khan, Danish; Hu, Pengfei; Habib, Salman; Waseem, Muhammad; Lin, Zhenzhi; Ahmed, Emad M.
Abstract: The inverter becomes an essential part in the distributed energy units, where an inductor–capacitor–inductor (LCL) filter is an up-to-date adoption for grid interfacing. However, the challenging issue of resonance related to the LCL-filter worsens the dynamic control characteristics and produces stability threat for the voltage source inverter system. The proper design of inverter control plays a substantial part in ensuring a steady state operation and a high quality of grid injected current according to grid connection codes. This paper offers a different design method of inverter control which alters the inner damping loop structure to enhance the damping and stability features of the inverter system. In the proposed solution, a modified compensator is employed through the LCL filter network and filter capacitor current feedback loop, the resultant augmented plant's output is then sent back at the reference point of a grid-connected inverter system to damp the unwanted resonance spike. This particular arrangement to form a damping loop is termed as parallel feedforward compensation. The damping loop is implemented by calculating the filter capacitor current, and a first order high-pass filter is employed as a damper in the suggested arrangement. Moreover, for comparative studies and analysis, the conventional filter capacitor current feedback active damping method is selected. In addition, the stability margins and control performance of the open current loop are examined under different filter parameters values. The substantial results of the suggested structure are quicker dynamic response, comparatively improved resonance damping, better tracking performance and higher delay compensation capability. A laboratory prototype is established to confirm the effectiveness of the suggested scheme on the bases of control performance and stability margins.